2021
DOI: 10.2478/orga-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Daily Affect in Leader-Member Exchange: A Multilevel Investigation in Public Health Administration

Abstract: Background and purpose: Although the critical role of affect in the leader-member relationship has been widely accepted, few studies investigated the impact of within-person affect variations in daily leader-member exchange (LMX) or addressed potential cross-level and intra-individual moderators of this relationship. This study examines the effects of followers’ positive and negative affect on their daily LMX in public health care organizations. The moderator roles of emotional labor and trait emotional intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…In addition, they found that LMX variation (as measured by the standard deviation [ SD ] of within-person LMX quality) moderated the mediation between LMX quality and well-being via the satisfaction of relatedness needs—such that it was stronger under low LMX variation. Çetin et al (2021) also report a daily diary study with responses collected over 5 days. They found that daily LMX quality predicted daily affect (positive and negative) and that this was moderated by trait emotional intelligence.…”
Section: Theoretical Framework and Development Of Hypothesesmentioning
confidence: 99%
“…In addition, they found that LMX variation (as measured by the standard deviation [ SD ] of within-person LMX quality) moderated the mediation between LMX quality and well-being via the satisfaction of relatedness needs—such that it was stronger under low LMX variation. Çetin et al (2021) also report a daily diary study with responses collected over 5 days. They found that daily LMX quality predicted daily affect (positive and negative) and that this was moderated by trait emotional intelligence.…”
Section: Theoretical Framework and Development Of Hypothesesmentioning
confidence: 99%